HIF-1α is a protective factor in conditional PHD2-deficient mice suffering from severe HIF-2α-induced excessive erythropoiesis. - Franke, K; Kalucka, J; Mamlouk, S; Singh, R; Muschter, A; Weidemann, A; Iyengar, V; Jahn, S; Wieczorek, K; Geiger, K; Muders, M; Sykes, A; et al. (2013)
Erythropoiesis must be tightly balanced to guarantee adequate oxygen delivery to all tissues in the body. This process relies predominantly on the hormone erythropoietin (EPO) and its transcription factor hypoxia inducible factor (HIF). Accumulating evidence suggests that oxygen-sensitive prolyl hydroxylases (PHDs) are important regulators of this entire system. Here, we describe a novel mouse line with conditional PHD2 inactivation (cKO P2) in renal EPO producing cells, neurons, and astrocytes that displayed excessive erythrocytosis because of severe overproduction of EPO, exclusively driven by HIF-2α. In contrast, HIF-1α served as a protective factor, ensuring survival of cKO P2 mice with HCT values up to 86%. Using different genetic approaches, we show that simultaneous inactivation of PHD2 and HIF-1α resulted in a drastic PHD3 reduction with consequent overexpression of HIF-2α-related genes, neurodegeneration, and lethality. Taken together, our results demonstrate for the first time that conditional loss of PHD2 in mice leads to HIF-2α-dependent erythrocytosis, whereas HIF-1α protects these mice, providing a platform for developing new treatments of EPO-related disorders, such as anemia.